Surgical and Experimental Pathology
Surgical and Experimental Pathology publishes essential research in molecular and cellular pathology, physiopathology, biomarkers of disease mechanisms, clinic-pathological entities and predictive response to therapy, with a special focus on translational approaches. It also brings together research addressing animal models, new and comparative methods, and case collections for specific regions or ethnic groups. The journal explores the pathophysiological and pathogenetic mechanisms of human disease, and aims to bridge the gap between molecular investigation and daily practice in surgical pathology.